THE INFLUENCE OF TRANSFORMATIONAL LEADERSHIP OF MANUFACTURING COMPANIES ON EMPLOYEE PERFORMANCE - Azizah Indriyani; Neli Hajar; Luth Luth (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2021)
The purpose of this research is to determine the effect of transformational leadership behavior in manufacturing companies on the performance of their employees. The object of this research was conducted at PT. Tyfountex Indonesia is engaged in textiles. The research approach uses a descriptive quantitative approach. This research was conducted using a survey method, namely research that takes a sample from a population and the instrument used is a questionnaire with judgmental sampling. The results of this study indicate that transformational leadership in manufacturing companies at PT. Tyfountex Indonesia has a significant and positive effect on employee performance both partially and simultaneously.